Innovative Transformations of Science-Intensive Industries in the National Economy of Azerbaijan: from Engineering to a Developed ICT Sector - Samira Abasova (Challenges and Issues of Modern Science)
Azerbaijan exports to other countries not only processed agricultural products, but also science-intensive and high-tech ICT services. If until 1990 the science-intensive industries of Azerbaijan were oil engineering, machine tool building, shipbuilding, instrument making, electrical engineering, then since 2013 Azerbaijan has become a space power and science-intensive and high-tech industries have become telecommunications and the ICT sector.